The Effect Of Counseling Using Pocket Book Media On Stunting Prevention On Mothers’ Knowledge Of Infants Aged 0–12 Months In The Working Area Of Puskesmas Perumnas II - Dessy Hidayati Fajrin; Novi Dwi Utami (PT. Edukasi Ahmad Kirang, 2026)
Background: Stunting is a national issue linked to chronic malnutrition, with Indonesia ranked second highest in Southeast Asia at 31.8% prevalence in 2020. At Puskesmas Perumnas II, cases rose from 76 in 2022 to 84 in 2023. Mothers’ limited knowledge about stunting prevention, particularly during the first 1,000 days of life, is a key contributing factor. Pocket books offer an attractive, concise, and portable alternative for delivering health education. Methods: Pre-experimental study using a one-group pretest-posttest design. A total of 50 mothers were recruited via consecutive sampling. Data were collected using a validated questionnaire (25 items, Cronbach’s α = 0.723). The Wilcoxon signed-rank test was used for analysis after normality testing confirmed non-normal distribution. Results: Pre-test median score was 72 (SD = 14.092; range 32–92). Post-test median score improved to 100 (SD = 6.355; range 76–100). Wilcoxon test yielded p-value = 0.000 (p < 0.05), indicating a statistically significant increase in knowledge. Conclusion: Pocket book–based health counseling significantly improved stunting prevention knowledge among mothers of infants aged 0–12 months. Puskesmas Perumnas II is recommended to integrate this media into routine health education programs.